Effects of Heat Waves During Post-natal Development on Mitochondrial and Whole Body Physiology: An Experimental Study in Zebra Finches - Ton, Riccardo; Stier, Antoine; Cooper, Christine E.; Griffith, Simon C. (Frontiers in Physiology, 2021)
Human-induced climate change is increasing the frequency, duration and intensity of heat waves and exposure to these extreme temperatures impacts individual physiology and performance (e.g. metabolism, water balance, growth). These traits may be susceptible to thermal conditions experienced during embryonic development, but experiments focusing on post-natal development are scant. Documented effects of heatwaves on whole-body metabolism may reflect changes in mitochondrial function, but most studies do not measure physiological traits at both the cellular and whole organism levels. Here, we exposed nests of zebra finches to experimentally simulated heat waves for 18 days after hatching and measured body mass, growth rate, whole-body metabolic rate, body temperature, wet thermal conductance, evaporative water loss and relative water economy of chicks at three ages corresponding to ectothermic (day 5), poikilothermic (day 12) and homoeothermic (day 50) stages. Additionally, we measured mitochondrial bioenergetics of blood cells 80 days post-hatch. While early-life exposure to heat wave conditions did not impact whole body metabolic and hygric physiology, body temperature was lower for birds from heated compared with control nests at both 12 and 50 days of age. There was also an effect of nest heating at the cellular level, with mitochondria from heated birds having higher endogenous and proton-leak related respiration, although oxidative phosphorylation, maximum respiratory capacity and coupling efficiency were not impacted. Our results suggest that early-life exposure to high ambient temperature induces programming effects on cellular-level and thermal physiology that may not be apparent for whole-animal metabolism.